Knowledge management in tourism organisations: proposal for an analytical model - Sequeira, Bernardete (2011)
Tourism is an activity-based service sector in which information and knowledge are fundamental to developing realistic strategies and business plans. This article presents a model that was developed in an investigation called “Organisational Knowledge Management in Tourism Organisations,” which was part of a doctoral degree in Sociology, Faculty of Economics, University of Algarve. This study investigated how Algarve tourist organisations manage knowledge by observing how they create, retain, share and use it. This empirical research is based on a study of three cases that used documental investigation, interviews and questionnaires and the analytic model that is introduced here. We present an analytic model that identifies the different stages of knowledge management (acquisition / knowledge creation, retention / storage, transfer / sharing and use) and the management practices that facilitate it (strategic management, organisational culture, structure and work processes, human resource policies, information systems and communications, evaluation of results and relationship with the environment outside the organisation) based on learning promotion.